Recurrent ascites in systemic lupus erythematosus treated with rituximab - a case report and review of pseudo-pseudo Meigs' syndrome - Sarah Compton; Sarah Luebker; DeAnna Baker Frost (Verduci Editore, 2021)
Systemic lupus erythematosus (SLE) is a chronic autoimmune and inflammatory disease with multisystem consequences. Pseudo-pseudo Meigs' syndrome (PPMS), or Tjalma syndrome, is a newly recognized manifestation of SLE that is characterized by increased CA-125 level, pleural effusion, and ascites without evidence of tumor. PPMS is relatively rare and likely under-recognized. To our knowledge, there are 11 published case reports about PPMS. In nearly half of the PPMS cases, ascites is the initial symptom of SLE. The pathophysiology of this syndrome is not completely understood but thought to be in part due to chronic inflammation, which is supported by symptoms abating with immunosuppression. We report a case of a 20-year-old woman with known SLE who developed recurrent large volume ascites, subsequently leading to the diagnosis of PPMS, requiring rituximab for additional immunosuppression. To our knowledge, this is the first case of using rituximab as a successful treatment for PPMS.